Kant´s Concept of Spontaneity within the Tradition of Aristotelian Ethics - Sgarbi, Marco (Studia Kantiana, 2009)
In Kant über Freiheit als Autonomie, Gerold Prauss suggests that in the middle of the 1760’s beside Rousseau’s influence on the concept of freedom in Kant’s moral writings, it is possible to find also the Aristotelian notion of spontaneity. The aim of the paper is to contextualize by means of the methodology of the Quellengeschichte Kant’s concept of spontaneity within the tradition of Aristo- telian ethics. In the first part of the paper I analyze Aristotle’s concept of spon- taneity and in the second its reception from Renaissance to Kantian philosophy. The third and fourth parts deal with spontaneity in Kant’s moral writings with the exemption of the Kritik der Urteilskraft, which involves and implies a much larger set of considerations on teleology and metaphysics. The conclusion is a critical assessment of Kant’s appropriation of Aristotle’s spontaneity.